Implementasi Metode Webuse Dalam Analisis Usability Pada Website Sistem Informasi Permohonan Online Dukcapil (SEMAIK) - Kadek Dwijayanti Komala Sari; Saikin Saikin; Mohammad Taufan Asri Zaen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The Department of Population and Civil Registration (Dukcapil) of Central Lombok Regency developed the SEMAIK website to enhance the quality of public services through digital platforms. This website provides official information such as local regulations, announcements, and government programs, while also facilitating communication between the government and the public. This study aims to evaluate the feasibility of the SEMAIK website using the WEBUSE method through an online questionnaire assessing usability aspects. The study involved 120 respondents, and the results showed that three out of four usability dimensions were rated as “Excellent”, with an overall average score of 87%, indicating a very high level of usability. However, the service aspect still needs improvement to achieve optimal user satisfaction. The contribution of this study is to provide a quantitative evaluation of the effectiveness of web-based public services and offer practical references for government institutions in enhancing the quality of digital services.